Correction to: Effects of Bang® Keto Coffee Energy Drink on Metabolism and Exercise Performance in Resistance-Trained Adults: A Randomized, Double-blind, Placebo-controlled, Crossover Study. Issue 1 (15th September 2020) - Harty, Patrick S.; Stratton, Matthew T.; Escalante, Guillermo; Rodriguez, Christian; Dellinger, Jacob R.; Williams, Abegale D.; White, Sarah J.; Smith, Robert W.; Johnson, Baylor A.; Sanders, Mark B.; Tinsley, Grant M.
Abstract : An amendment to this paper has been published and can be accessed via the original article.